MEASURES FOR SANITARY AND HYGIENIC PROTECTION OF THE SOIL - Tuxtaeva M.M (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Soil is the most important wealth of nature, it is the most porous, fertile part of the Earth's crust. It was formed as a result of physical, chemical and biological processes that took place in the lithosphere, hydrosphere, atmosphere and biosphere in connection with each other for a long time.